Posterior segment findings in a patient with a CDHR1 biallelic pathogenic variant - Yusuf Kemal Durlu; Sezin Canbek (American Journal of Ophthalmology Case Reports)
Purpose: To report the posterior segment findings in a case with a biallelic CDHR1 frameshift pathogenic variant at chromosome 10 c.616del exon7 p.(His206Thrfs∗61). Observations: A 25-year-old man was diagnosed with retinitis pigmentosa (RP). Fundus examination disclosed bone spicule pigmentation, arteriolar attenuation, peripheral/midperipheral retinal atrophy, and scattered retinal pigment epithelial atrophy/mottling. The wavy appearance of the protrusions located at the inner retinal surface was dispersed from the macula to the midperipheral/peripheral retina in a distinct uniform pattern as observed on structural optical coherence tomography (OCT) images and en-face OCT; the protrusions led to non-cystic petaloid maculopathy. In addition, numerous hyperreflective dots were noticed at the inner limiting membrane level of the temporal macular region. Structural OCT disclosed an increase in choroidal thickness. OCT angiography showed normal retinal vessel density at the superior vascular complex, whereas the deep vascular complex showed a significant reduction in retinal vessel density. The microperimetry showed an abnormal average threshold and abnormal macular integrity, whereas the stability of fixation was completely fulfilled. Photopic/scotopic and multifocal electroretinography findings disclosed subnormal recordings. Psychiatric consultation revealed major depressive disease requiring hospitalization. Conclusions and importance: Posterior segment findings of RP rather than macular dystrophy were observed in our patient. Inner retinal surface remodeling leading to non-cystic petaloid maculopathy and distinct uniform wavy protrusions extending to the midperipheral/peripheral retinal regions might reveal the involvement of Müller cells in our patient with cadherinopathy. A syndromic association may exist in our patient with a CDHR1 frameshift pathogenic variant and major depressive disease.